Role of nNOS in the automatic control of cardiac excitability in cardiac physiological and pathophysiological states - Heaton, D; Heaton, Daniel Anthony (2005)
The studies presented in this thesis were undertaken in an attempt to further understand the role of nNOS-derived nitric oxide (NO) in the autonomic control of heart rate in health and disease. Chapter One gives a general overview of mechanisms involved in the generation of sinus rate, and illustrates the physiological modulation of heart rate (HR) by the autonomic nervous system. The roles of NO in parasympathetic and sympathetic control of HR are discussed, together with the clinical significance of autonomic dysfunction in cardiovascular disease. The potential use of nNOS gene transfer as a novel intervention to restore normal autonomic balance is introduced. Chapter Two provides a detailed technical account of the experiments performed in this thesis. Techniques for adenoviral gene transfer of nNOS to the right atrium and vagus are described, together with methods used for molecular, histological, and physiological phenotyping of transfected animals. In addition the preparation of animals for chronic infusion of angiotensin II (ATII) is outlined. Chapter Three illustrates up-regulated nNOS expression in intracardiac cholinergic neurons of the guinea pig 5 days after right atrial injection of Ad.nNOS. Functionally this resulted in a pre-junctional enhancement of right vagal function (assessed in vivo and in vitro) since HR responsiveness to the muscarinic agonist carbachol was unaffected. In addition HR responsiveness to β-adrenergic stimulation was attenuated after nNOS gene transfer. Vagal responsiveness of nNOS transfected animals was normalised by acute pharmacological NOS inhibition. In contrast, vagal responsiveness was unaffected by gene transfer of enhanced green fluorescent protein (Ad.eGFP). Chapter Four demonstrates rapid functional gene expression, resulting in enhanced parasympathetic function, after targeted nNOS gene transfer to preganglionic right vagal neurons of the pig. Baroreflex sensitivity and HR responsiveness to right vagal stimulation were significantly increased within 7 hours. In contrast, responsiveness of left vagi injected with Ad.eGFP was unchanged over time; similar results were observed after sham (saline) injection. These results demonstrate a role for NO in facilitating vagal neurotransmission at the pre-/post-ganglionic synapse of the pig, and show that nNOS gene transfer provides a novel intervention to acutely modulate cardiac autonomic responsiveness. Chapter Five demonstrates impaired peripheral vagal function in the spontaneously hypertensive rat (SHR), and shows increased vagal responsiveness in vivo after nNOS gene transfer; suggesting that this intervention can be used to "rescue" impaired peripheral parasympathetic dysfunction in cardiovascular disease. Responsiveness of isolated atria to carbachol was unaffected by nNOS gene transfer in the SHR, but was increased by Ad.nNOS in the normotensive Wistar Kyoto rat (WKY); indicating a possible species difference in post-junctional muscarinic signalling between the guinea pig and rat, and suggesting a possible alteration of this pathway in hypertension. Chapter Six shows hyper-responsiveness of the sinus node of the SHR to β-adrenergic stimulation, and suggests that this results from elevated current density of ICaL in isolated pacemaking cells. nNOS gene transfer normalised adrenergic responsiveness of the SHR via attenuation of ICaL but had relatively little effect in the WKY, suggesting that nNOS-mediated regulation of β-adrenergic responsiveness may be most significant when the signalling pathway is abnormally activated. Chapter Seven demonstrates the pre-junctional vagolytic action of acutely administered ATII in the guinea pig, and suggests that this is mediated via activation of PKC-dependent signalling mechanisms. Chronic administration of a sub-pressor dose of ATII results in a compensatory increase in vagal function via up-regulation of nNOS expression, which may serve to maintain normal autonomic balance during the early stages of hypertension. However, this mechanism fails after chronic exposure to a pressor dose of ATII and the onset of pathophysiological ventricular remodelling. Chapter Eight summarises these experimental results, places them in a physiological context, and outlines potential avenues for future research.